Essentials of entrepreneurship and small business management - Zimmerer, Thomas W.; Scarborough, Norman M. (New Delhi : Pearson Education, 2007)
Business
Keywords: Business Management; Entrepreneurship; Small business; Business ownership; Business Plan; Financial Plan; Management succession